Beyond the Comtean Schema: The Sociology of Culture and Cognition Versus Cognitive Social Science1. Issue 4 (December 2014) - Lizardo, Omar
<x xml:space="preserve">Abstract</x> In this essay, I argue that the very form of the grammatical construction "a sociology of culture and cognition" (which is a specification of the more general schema "a sociology of [X]") is symptomatic of a deeply entrenched form of "Primitive Classification" (which I will refer to as the "Comtean schema") that governs the way in which sociologists conceive of their place in, and engage with other denizens of, the social science landscape. I will also argue that while this style of disciplinary engagement might have worked in the past when it came to dealing with the standard (nineteenth‐century) social science disciplines and even some late‐twentieth‐century upstarts, it will not work as a way to engage the now‐sprawling postdisciplinary field that I will refer to as "Cognitive Social Science" (CSS). The takeaway point is that if sociologists want to be part of CSS (and it is in their interest to be part of it because this constitutes the future of the behavioral sciences), then they will have to give up the Comtean‐schematic thought style.